Humanizing childbirth for Muslim Women: call for a shariah compliant guideline / Norazlina Abdul Aziz …[et al.] - Abdul Aziz, Norazlina; Ibrahim, Irini; Abdul Raof, Nurazlina; Abdullah, Rozlinda; Yahaya, Nur Asma; Ahmad, Nurullhuda (Academy of Contemporary Islamic Studies (ACIS), 2017)
There are many complaints made by Muslim women on the dilemma that they faced during the childbirth process. Among the complaints is the issue of aurah, the rights for them to have female doctors and to be pre-informed on the usage of non-halal medicine. Currently there are no specific guidelines or regulations adopted by the public and private hospitals to uphold these rights of Muslim women during childbirth. Although the childbirth process can be categorized as the situation of dharurah or emergency where exception to the general Islamic rulings is applicable, yet the exception will be lifted when the situation of dharurah ceased to exist. Labour processes involve three stages that include the pre-childbirth, during childbirth and post-childbirth. The question is whether all three stages are qualified to be categorized as dharurah thus making it unnecessary to propose a guideline to address the issue of Muslim women during childbirth. In answering this question, the study will analyse the current practices in the private and public hospital during the three stages of childbirth with the aim of identifying the protection of rights given to the Muslim women in upholding their religious practice. The concept of dharurah will be discussed in applying it to the three stages of childbirth. The study adopts qualitative methods that involve arm-researcher method and semi-structured interviews. The arm-researcher approach delved into the current guideline (if any) applicable to doctors and medical assistance during childbirth in the private and public hospitals and the relevant laws. Meanwhile semi-structured interviews were conducted with selective respondents consisting of the medical practitioner, legal practitioner, and academicians. The study proposed for a guideline that can govern the conduct of medical practitioners and childbirth assistance in attending Muslim women during the three stages of childbirth.